How does Martin Buber's concept of I-Thou dialogue inform the theory and practice of relational leadership? - Reitz, Megan (Cranfield University, 2014)
This thesis explores the possibility of dialogue between leader and follower in order to further develop the theory and practice of relational leadership. It draws from and contributes to Relational Leadership Theory (Uhl-Bien 2006) and Buber’s concept of ‘I- Thou’ dialogue (Buber 1958). Using first-person and co-operative inquiry methods (Reason and Bradbury 2008b) the ‘space between’ (Bradbury and Lichtenstein 2000, Buber 1958) leader and follower is explored in order to reveal the complexities inherent within leadership relations. Four main findings are detailed which enrich our understanding of how leadership relations operate from ‘within living involvement’ (Shotter 2006). Firstly, the quality of leader-follower encounter could be affected by levels of ‘busyness’ and the ensuing assessment and prioritising process. Secondly, the pressure to ‘seem’ rather than ‘be’ may strengthen the construction of a façade which might be dismantled, in part, through disclosure, though this may feel extremely risky given organisational ‘rules’. Thirdly, mutuality between leader and follower may be crucially influenced by the way in which ‘leader’, ‘leadership’ and ‘power’ are constructed in the between space. Finally, ineffable dialogic moments may occur through sensing a particular quality of encounter amidst and despite the complexity of a myriad of micro-processes vying for attention in the between space. This thesis contributes a further strand to RLT constructionist work focused on the quality of leader-follower encounter which has not been previously revealed. Leadership constructs and macro-discourses relating to power, ‘busyness’ and the need for ‘worthwhile meetings’ encourages transactional relating. Consequently, opportunities for genuinely encountering others in organisational settings are suffocated. This holds important implications for ‘leaders’ and ‘followers’ who wish to creatively address pressing organisational issues in the 21st century through dialogue. Fundamentally this thesis suggests we pause to consider the implications that the nature of our encounters in our work-life have upon us as human beings wishing to know what it is to be fully human.
Keywords: Relational leadership; dialogue; Martin Buber; first-person inquiry; co-operative inquiry